Highly efficient room-temperature phosphorescence achieved by gadolinium complexes. Issue 40 (23rd September 2019) - Sun, Boxun; Wei, Chen; Wei, Huibo; Cai, Zelun; Liu, Huanyu; Zang, Zhiyu; Yan, Wenchao; Liu, Zhiwei; Bian, Zuqiang; Huang, Chunhui
Abstract : Highly efficient room-temperature phosphorescence achieved by employing gadolinium complexes, with emission color from blue to orange. Abstract : A new family of room temperature phosphorescent materials with emission lifetimes in microseconds has been reported in this work. Phosphorescence of gadolinium complexes with emission color from blue to orange has been obtained at room temperature with a maximum photoluminescence quantum yield of 66%, benefiting from appropriate molecular structures and favorable encapsulation methods.